PENGEMBANGAN BAHAN AJAR SCRAPBOOK TEMA 5 SUBTEMA 1 KOMPONEN EKOSISTEM KELAS V SDN TANAMERA 1: PENGEMBANGAN BAHAN AJAR SCRAPBOOK TEMA 5 SUBTEMA 1 KOMPONEN EKOSISTEM KELAS V SDN TANAMERA 1 - Milinda Sari, Sherliy; Rahmad Wijaya, Bagus (Universitas Islam Malang, 2024)
The objectives of this development research were (1) To find out the validity of Scrapbook teaching materials for class V theme 5 sub-themes 1 ecosystem component, (2) To find out the effectiveness of Scrapbook class V teaching materials theme 5 sub-themes 1 ecosystem component as seen from the results of observation sheets of teacher activity, observation sheets of student activities and student learning outcomes (3) To find out the attractiveness of Scrapbook teaching materials for class V theme 5 sub-themes 1 ecosystem component seen from the teacher and student response questionnaire. This study uses Research and Development (R&D) research and development methods with the ADDIE research model. This research was conducted in class V with a total of 25 students. Based on the data obtained by the researcher, the validity of teaching materials obtained a percentage of 95.8% with a very valid category. Effectiveness is measured based on the results of observations of teacher activity and student activity. In the small group trial the results of observing teacher activity got a percentage of 90.9% and the results of student activities got a percentage of 88.3% with a very effective category. 100% for classical completeness results from student learning outcomes. In the large group trial the results of observing teacher activity got a percentage of 90.9%, the results of observing student activities got a percentage of 88.6% in the very effective category and the results of students' cognitive learning tests got a percentage of 90% declared complete. Interestingness was measured based on the results of the small group and large group teacher response questionnaires which obtained a percentage of 92.5% in the very attractive category. The results of the student response questionnaire show that the percentage is 95% with a very interesting category . Keywords: Teaching materials, Ecosystem component, Scrapbook.